2004
DOI: 10.1152/jn.00519.2003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Impedance Control for Task Achievement in the Presence of Signal-Dependent Noise

Abstract: There is an infinity of impedance parameter values, and thus different co-contraction levels, that can produce similar movement kinematics from which the CNS must select one. Although signal-dependent noise (SDN) predicts larger motor-command variability during higher co-contraction, the relationship between impedance and task performance is not theoretically obvious and thus was examined here. Subjects made goal-directed, single-joint elbow movements to either move naturally to different target sizes or volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 42 publications
12
114
3
Order By: Relevance
“…This matches with previous work [31][32][33], where subjects performed a positioning task with elbow rotations and used increased stiffness as the target circle size decreased. In general, this finding of increased stiffness with greater accuracy requirement correlated with Hogan's theory of robotic manipulation and impedance control [18].…”
Section: Discussionsupporting
confidence: 89%
“…This matches with previous work [31][32][33], where subjects performed a positioning task with elbow rotations and used increased stiffness as the target circle size decreased. In general, this finding of increased stiffness with greater accuracy requirement correlated with Hogan's theory of robotic manipulation and impedance control [18].…”
Section: Discussionsupporting
confidence: 89%
“…However, tasks used in motor control experiments such as reaching movements (Morasso 1981;Osu et al 2003;Uno et al 1989), force field learning (Burdet et al 2001;Shadmehr and Mussa-Ivaldi 1994), and movements through via-points (Flash and Hogan 1985;Uno et al 1989) are limited in their ability to differentiate effort from error minimization (O'Sullivan et al 2009): Noise and thus error generally increase monotonically with motor command (Jones et al 2002;Osu et al 2004), such that error and effort are in one-to-one relationship. These tasks thus feature a single optimum of error and effort in which optimization has been computed using linear optimal control (Todorov and Jordan 2002) or nonlinear optimization with constraints (Biess et al 2007) or by gradient descent (Franklin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Another class of reaching models are stochastic models that take into account the noise inherent to the motor system. It has been consistently observed that the standard deviation of neuromotor commands increases with its mean (Sutton and Sykes 1967;Schmidt et al 1979;Clamman 1969;Matthews 1996;St-Amant et al 1998;Clancy and Hogan 1999;Osu et al 2004). In line with this evidence, it was suggested that the brain minimizes the variance of the final arm position in the presence of such signal-dependent motor noise (Harris and Wolpert 1998;Hamilton et al 2002).…”
Section: Computational Approachmentioning
confidence: 92%